Validação de metodologia analítica empregando coluna curta em cromatografia gasosa para a determinação de ésteres alquílicos - Silva, Filipe Lins da (2016)
Biodiesel is a mixture of alkyl esters produced from vegetable or animal oils and fats. It is one of the most currently produced biofuels and an alternative renewable energy source to fossil fuels. Many methods have been applied to biodiesel analysis in terms of alkyl esters. In this context, was validated an analytical methodology based on gas chromatography with a short column, detection by flame ionization and intern normalization with response factor to quantify the fatty acids (methyl and ethyl) esters. The validated method was used to analyze biodiesel produced from several raw materials, which were previously characterized with respect to the fatty acid composition. For validating the methodology in use at the laboratory, the method was employed for the analysis of twenty samples of methyl biodiesel and twenty samples ethyl biodiesel produced from soybean oil and this method demonstrated selectivity to separate and identify the chemical species present in the samples. When the method was submitted to some variations at the sample preparation process, the method remained sensitive and robust. Based on the parameters of the calibration curve, the limits of detection and quantification were LD = 0.0067 gmL-1 and LQ = 0.0204 gmL-1. The method also showed a great precision when carried out successive analyzes conducted by different analysts, an excellent accuracy when compared with other reference methods and during recovery studies. By comparing the results, the validated method was compared to two reference methodologies: a gas chromatography methodology based on the European standard (EN 14103) indicated by the National Agency of Petroleum, Natural Gas and Biofuels, and a method based on high-performance liquid chromatography (HPLC-UV). In these comparisons it was obtained the correlation coefficient, r = 0.99, for the methyl soybean biodiesel analyzes in both compare situations. By comparing the results of ethyl soybean biodiesel analyzes, the validated method presented an r = 0.99 to both situations, using the HPLC-UV and GC-EN 14103 methods. In the study of other raw materials at producing biodiesel, the validated method was compared with EN 14103 methodology and presented compatible results to the EN 14103 methodology for determining methyl esters content in biodiesel of cotton, sunflower and palm.